Dynamics of hepatic steatosis resolution and changes in gut microbiome with weight loss in nonalcoholic fatty liver disease. (4th January 2021) - Behari, Jaideep; Graham, Lisa; Wang, Renwei; Schirda, Claudiu; Borhani, Amir A.; Methé, Barbara A.; Li, Kelvin; Morris, Alison; Luu, Hung N.; Palmieri, Sabrina; Yuan, Jian‐Min
Abstract: Background: Weight loss is recommended as the primary treatment for nonalcoholic fatty liver disease (NAFLD). However, the magnitude and velocity of hepatic steatosis resolution with weight loss is unclear, making it difficult to counsel patients seeking weight loss for treatment of NAFLD. The aim of this study was to determine the rate of hepatic steatosis improvement and stool microbiome changes associated with rapid diet‐induced weight loss in NAFLD. Methods: Fourteen NAFLD patients (mean ± standard deviation, body mass index [BMI] 36.4 ± 4 kg/m 2 ) enrolled in a 12‐week meal replacement program underwent frequent measurement of Fibroscan‐controlled attenuation parameter (CAP). Magnetic resonance imaging (MRI‐Dixon method) for hepatic fat quantitation and stool microbiome analysis (16S rRNA gene sequencing) were completed in 11 subjects at baseline and Week 12. Results: At Week 12, mean (95% confidence interval) weight loss was −13.4 (−15.2, −11.5)% and CAP score −26.6 (−35.6, −17.6)% (both Ps  < 0.001). CAP scores changed at a rate of −4.9 dB/m/kg (−30.1 dB/m per unit BMI) in Weeks 1–4 and −0.6 dB/m/kg (−2.4 dB/m per unit BMI) in Weeks 8–12. MRI‐determined hepatic fat fraction decreased by −74.1% ( p  < 0.001) at a rate of −0.51%/kg (−3.19% per unit BMI), with complete steatosis resolution in 90% patients. BMI change was associated with decreased stool microbial diversity (coefficient = 0.17; Shannon Index), increased abundance of Prevotella_9 (Bacteroidetes; coefficient = 0.96) and decreased abundance of Phascolarctobacterium (Firmicutes; coefficient = −0.42) (both Ps  < 0.05). Conclusions: Diet‐induced intensive weight loss is associated with rapid improvement and complete resolution of hepatic steatosis and decreased stool microbial diversity. These findings highlight the dynamic nature of hepatic fat and may help clinicians to develop evidence‐based treatment goals for patients with NAFLD and obesity who undertake weight loss interventions. Further research is warranted to understand the effects of intensive weight loss and gut microbiome changes on long‐term NAFLD resolution.